2011
DOI: 10.1111/j.1365-2028.2011.01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Population status and human impact on the endangered Swayne’s hartebeest (Alcelaphus buselaphus swaynei) in Nechisar Plains, Nechisar National Park, Ethiopia

Abstract: The study on the population status and human impacts on the endemic and endangered Swayne's hartebeest (Alcelaphus buselaphus swaynei) was carried out in Nechisar Plains, Nechisar National Park, between 2009 and 2010. Direct and total count methods were applied in the population census. Data collected since 1967 were also examined to indicate trends of Swayne's hartebeest populations and their translocation status. In eight illegal Guji Oromo settlements, a total of 134 household samples were identified for gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…However, habitat disturbance was the major causes identified as HWC in this study. The result was in agreement with different studies in Ethiopia and other countries in the world (Hill et al, 2002;Barnes et al, 2003;Pariela, 2005;Blair, 2008;Datiko and Bekele, 2011;Mwamidi et al, 2012;Edward and Frank, 2012) which reported increased habitat disturbance as the cause of HWC. Jones (2012) reported that habitat destruction and fragmentation was the main cause of human primate conflict in Indonesia.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, habitat disturbance was the major causes identified as HWC in this study. The result was in agreement with different studies in Ethiopia and other countries in the world (Hill et al, 2002;Barnes et al, 2003;Pariela, 2005;Blair, 2008;Datiko and Bekele, 2011;Mwamidi et al, 2012;Edward and Frank, 2012) which reported increased habitat disturbance as the cause of HWC. Jones (2012) reported that habitat destruction and fragmentation was the main cause of human primate conflict in Indonesia.…”
Section: Discussionsupporting
confidence: 82%
“…This agrees with the studies in other parts of Ethiopia. According to Datiko and Bekele (2011) and Mwamidi et al (2012), the number and type of damage caused by wildlife vary based on the species, the time of year, and the availability of natural prey and crop raiding species. Even though both agricultural damage and livestock depredation were observed in the study area, crop loss due to wildlife was the most serious problem in the study sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maze National Park, Ethiopia, weighing between 100 to 200 kg [47]. It was once widely distributed in Ethiopia, Somalia and Djibouti [48], but currently its range is confined to Ethiopia [49][50][51] and listed as endangered sub-species by IUCN Red list [52]. In our recent study, we documented the largest…”
Section: Swayne's Hartebeest (Alcelaphus Buselaphus Swaynei) Is One Omentioning
confidence: 99%
“…Swayne's hartebeest (Alcelaphus buselaphus swaynei) is a large body-sized herbivore weighing between 100 and 200 kg [46]. It was once widely distributed in Ethiopia, Somalia and Djibouti [47], but currently its range is confined in two protected areas: Senkele Swayne's Hartebeest Sanctuary and Maze National Park in Ethiopia [46,48,49] and listed as endangered sub-species by IUCN Red list [50]. In our recent study, we documented the largest population of Swayne's hartebeests in Maze National Park (Misganaw et al unpublished), which remains unstudied and receives little attention from the scientific community.…”
Section: Introductionmentioning
confidence: 99%